2012
DOI: 10.1177/0300985812450718
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotypical Characterization of Macrophages in Rat Bleomycin-Induced Scleroderma

Abstract: Scleroderma is a skin disorder characterized by persistent fibrosis. Macrophage properties influencing cutaneous fibrogenesis remain to be fully elucidated. In this rat (F344 rats) model of scleroderma, at 1, 2, 3, and 4 weeks after initiation of daily subcutaneous injections of bleomycin (BLM; 100 ml of 1 mg/ml daily), skin samples were collected for histological and immunohistochemical evaluations. Immunohistochemically, the numbers of cells reacting to ED1 (anti-CD68; phagocytic activity) and ED2 (anti-CD16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Cutaneous macrophage infiltration has been suggested to be associated with refractory aGVHD and poor prognosis (16). Alternatively, activated macrophages (CD163 + ) have been previously shown to be present in both humans (17) and rats with systemic sclerosis (18). Additionally, macrophages displaying an M2 phenotype are present in the skin (19) and lungs of patients with systemic sclerosis (20).…”
Section: Introductionmentioning
confidence: 99%
“…Cutaneous macrophage infiltration has been suggested to be associated with refractory aGVHD and poor prognosis (16). Alternatively, activated macrophages (CD163 + ) have been previously shown to be present in both humans (17) and rats with systemic sclerosis (18). Additionally, macrophages displaying an M2 phenotype are present in the skin (19) and lungs of patients with systemic sclerosis (20).…”
Section: Introductionmentioning
confidence: 99%
“…2). TGF-␤1 is well known to be an inducer of myofibroblasts from the progenitors, and its expression is increased in organs undergoing fibrogenesis (Golbar et al, 2011;Golbar et al, 2013;Juniantito et al, 2013;Kang et al, 2007;Liu, 2006). TGF-␤1 mRNA expression was increased in the present CDDP-induced kidney lesions.…”
Section: Renal Fibrosis Induced By Cddp and Expression Of Bmp-6 Opn mentioning
confidence: 65%
“…In a rat model of bleomycininduced scleroderma, immunohistochemical staining of skin lesions showed that galectin-3 could be expressed in CD68 + , CD163 + , and MHC class II + macrophages and myofibroblasts. [37] Human studies showed galectin-3 serum levels were significantly decreased in patients with early stage diffuse cutaneous SSc than in normal control. However, galectin-3 serum levels were higher in SSc patients with digital ulcers/elevated right ventricular systolic pressure than in patients without these signs.…”
Section: Sclerosismentioning
confidence: 97%
“…The profibrotic function of galectin‐3 in fibrosis development in different organs, including liver, lung, heart, kidney, and blood vessels, was mentioned (reviewed in ). In a rat model of bleomycin‐induced scleroderma, immunohistochemical staining of skin lesions showed that galectin‐3 could be expressed in CD68 + , CD163 + , and MHC class II + macrophages and myofibroblasts . Human studies showed galectin‐3 serum levels were significantly decreased in patients with early stage diffuse cutaneous SSc than in normal control.…”
Section: Fibrotic Disordersmentioning
confidence: 99%
See 1 more Smart Citation